Analisa Tingkat Literasi Keuangan dan Sumber Daya Manusia dalam Meningkatkan Manajemen Keuangan UMKM melalui Kinerja Keuangan - Dea Mirela; Junaedi Junaedi; Riyanti Riyanti (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2026)
This study focuses on exploring how financial ability and human resource quality influence the financial performance of MSMEs, both directly and indirectly thru financial management as a mediating variable. This study applied a quantitative method survey approach with emphasis on primary data from questionnaires distributed to 125 MSME actors. Data analysis employed SPSS statistics with a multiple linear regression model and the sobel mediation test. The research the results show that financial literacy and human resource quality Provides a positive and meaningful contribution to financial performance. Financial management acts as a partialintervening variabel, strengthening the influence of financial literacy and human resources on financial performance. This investigation implies that improving financial ability and the quality of human resources, supported by good financial management practices, can enhance the financial performanceofSMEs.